Conhecimentos de geografia no curso de pedagogia da Unisul: implicações na formação de professores pedagogos - Beckhauser, Ingryd Bianchet Marcelino (2019)
This research has as problematic to understand what knowledge of Geography is worked in the course of Pedagogy. It has as general objective to know the knowledge of Geography worked in the initial formation of teachers in the course of Pedagogy of Unisul and its implication in the formation of this professional. And as specific objectives: to identify the concepts of Geography proposed in the menus of the subjects in the course of Pedagogy; identify in the programmatic contents those referring to Geography; to establish a relationship between the contents present in the Course Project with the main concepts of the Geography area; to verify the bibliographical references related to Geography and to reflect on the implications of the contents proposed in the Unisul Course Project in the education of the pedagogue. The research has as a theoretical-methodological conception guiding Historical-Dialectical Materialism. The source used in this research was the Pedagogical Project of the Unisul Pedagogy Course. In it, all the menus of the Learning Units (disciplines) of the course were analyzed, highlighting those that contained contents of the Geography or related to it, besides the references in the teaching plans of the Units that contained Geography contents. In this process, we highlight the contents of Geography or related to it from the definitions of renowned Geography authors such as Castrogiovanni, Callai e Kaercher (2006). Among the contents considered indispensable for this training, we highlight: location, orientation, representation, landscape, place and territory, and valuing some tools, such as cartography, that instrumentalizes the student to be a reader and active mapper, aware of the subjective perspective in the choice of the mapped fact, marked by value judgment. The results of the research showed that the knowledge of Geography considered according to Castrogiovanni, such as location, orientation, representation, landscape, place and territory and cartography, appear in the learning units of the Pedagogy course as structuring certifications, that is, they are compulsory courses of the course that allow the pedagogue a solid formation in the discipline of Geography, providing him with the conditions to teach the bases of geographic knowledge for the children of the initial years of Elementary School.